2009
DOI: 10.1017/s1368980009991753
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an integrated community-based micronutrient and health programme on stunting in Malawian preschool children

Abstract: Objective: To assess the impact of the 1996-2005 integrated community-based micronutrient and health (MICAH) programme on linear growth retardation (stunting) in Malawian preschool children living in rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…However, it has been shown that multidisciplinary programmes can combat stunting over a longer time period (54) . This finding was confirmed in studies in Malawi, Ethiopia and Haiti evaluating a community-based programme addressing stunting over a period of 5-8 years (55)(56)(57) .…”
Section: Discussionsupporting
confidence: 52%
“…However, it has been shown that multidisciplinary programmes can combat stunting over a longer time period (54) . This finding was confirmed in studies in Malawi, Ethiopia and Haiti evaluating a community-based programme addressing stunting over a period of 5-8 years (55)(56)(57) .…”
Section: Discussionsupporting
confidence: 52%
“…A few studies [16, 17] carried out in similar settings also reported that counselling mothers on child feeding practices is associated with overall improvement in optimum infant and child feeding practices. Although, some studies found that maternal nutrition counselling results in reduced childhood stunting [19, 20], other studies [43, 44] reported that nutrition counselling were ineffective in reduction of stunting among young children. However, it was also reported through conducting a meta-analysis that nutrition education is effective in reducing stunting among young children when it is complemented with interventions such as food or micronutrient supplementation or nutrition safety net programs [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, the same combinations of interventions were not similarly effective in Ethiopia, Haiti, India, Malawi or Mexico. 20 26 28 30 31 The difference may be explained by the need for more secure targeting of younger children from rural household, and also the effects of other programmes or interventions in either the same or a neighbouring community. It is clear that in addition to geographical location, the organisation, administration and delivery of the intervention, as well as the population being targeted has an effect on the overall effectiveness of the intervention.…”
Section: Discussionmentioning
confidence: 99%